A comparison of Green policy ambitions by examining Slovak and Hungarian small enterprises - János Varga; Ágnes Csiszárik-Kocsir; Mónika Garai-Fodor (Administrative Sciences, 2024)
Climate change is a problem for all of us and must be tackled as a priority, not just as the responsibility of national economic policies. It has not only environmental but also economic and social consequences. Climate change can change people's daily lives, strongly affecting their health and mood. It will reshape the way the economy works, affect the way we use our resources, and impact on the state of our environmental assets. Emissions are one of the most important causes of global warming and are largely responsible for adverse changes in the ecosystem. Many businesses will need to fundamentally transform their operations to become climate neutral. Entire sectors will have to innovate and abandon current (polluting) solutions in order to allow businesses to do business in new and greener ways. This requires money, skills, knowledge, innovation and of course, leadership commitment. This paper sets out to examine the business case for greening. The study focuses on the behavior of enterprises and draws conclusions on environmental awareness by comparing two countries. The paper presents the results of quantitative primary research on a Hungarian and a Slovak sample, using a pre-tested standardized questionnaire survey. We analyzed responses from 427 enterprises in the Hungarian sample and 181 in the Slovak sample. The results show which enterprises in each country can be relied on most to implement sustainable, green policies and what the main challenges are in terms of promoting more sustainable behavior among enterprises in the two countries under study.
Keywords: 350; sustainability; green deal; business; green transition